ANALISIS POPULASI DAN HABITAT BANGAU TONGTONG (Leptoptilos javanicus Horsfields 1921) DI TAMAN NASIONAL ALAS PURWO, JAWA TIMUR - Sutiawan, Riki; Hernowo, Jarwadi Budi (Media Konservasi, 2016)
Alas Purwo National Park (APNP) is a conservation area which still has a natural habitat and population of lesser adjutant in Indonesia. The bird is considered vulnerable IUCN red list 2016 and protected by government regulation of Republic Indonesia No.7/1999. The study was aim to analyze the population (individual number, sex ratio, age structure and natality) and it’s habitat including nesting. The observation was focused in Rowobendo Resort APNP (Sadengan garzing area, tropical rain forest surrounding Sadengan garzing area and mangrove of Sumber Gedang) with concentration count method for population and habitat analysis used method for decribed habitat condition. This study showed that individuals number of the bird are 21 individu consist of adult birds with sex ratio 1:1 (male:female). Potential natality reflected by their eggs in the nest (three eggs), but did not successfully being hatching due to predator attack. The population parameter showed that the bird population is productive The bird using Sadengan grazing area to find feed, lowland forest used to resting and nesting and mangrove used to resting and seaching food. The chracteristik of nesting site available of emergent trees which have crown with aubrevile architecture and the trees closed to habitat for search food. The searching food habitat have characteristic is open area with mudy or grazing area whic have  potential their food. Keywords: habitat, lesser adjutant, population